2007
DOI: 10.3354/meps335095
|View full text |Cite
|
Sign up to set email alerts
|

Mapping anthropogenic nitrogen through point sources in coral reefs using δ15N in macroalgae

Abstract: To trace anthropogenic N from sewage outfalls in coral reefs of Nanwan Bay, southern Taiwan, we analyzed tissue N, C/N ratio, and δ 15

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 29 publications
1
27
1
Order By: Relevance
“…Similar trends have been reported in other regions of the world, such as French Polynesia [3], Australia [9][10][11], Taiwan [12], and the Baltic Sea [13]. However, most of these studies dealt with sewage outfalls [10][11][12][13], river water [8,11], groundwater seepage [8], and/or effluents from inshore shrimp farms [3,9,11] as nitrogen loading sources. In some studies, nitrogen loading was determined using seagrasses inhabiting muddy to sandy substrata as nitrogen indicators by analyzing their d 15 N [11,14,15].…”
Section: Introductionsupporting
confidence: 52%
“…Similar trends have been reported in other regions of the world, such as French Polynesia [3], Australia [9][10][11], Taiwan [12], and the Baltic Sea [13]. However, most of these studies dealt with sewage outfalls [10][11][12][13], river water [8,11], groundwater seepage [8], and/or effluents from inshore shrimp farms [3,9,11] as nitrogen loading sources. In some studies, nitrogen loading was determined using seagrasses inhabiting muddy to sandy substrata as nitrogen indicators by analyzing their d 15 N [11,14,15].…”
Section: Introductionsupporting
confidence: 52%
“…Macroalgae take up N from their environment with no evidence of N fractionation (Cohen and Fong, 2005), therefore their d 15 N values likely represent the integration of all available N sources. Macroalgae growing adjacent to sewage outfalls frequently have enriched d 15 N values ranging from 9 to 15% (Gartner et al, 2002;Costanzo et al, 2005;Lin et al, 2007). To date, the highest reported macroalgal d 15 N value is 50.1 % from samples of Ulva lactuca grown over warm, freshwater seeps on a nearshore reef at Kahekili on Maui (Dailer et al, 2010).…”
mentioning
confidence: 96%
“…Globally, over the past few decades, sources of anthropogenic N have been detected by investigating the isotopic signature of N ( 15 N: 14 N, expressed as d 15 N; Eq. 4) (Gartner et al, 2002;Costanzo et al, 2005;Lin et al, 2007;Risk et al, 2009;Dailer et al, 2010Dailer et al, , 2012. This is possible because different N sources have distinct d 15 N signatures.…”
mentioning
confidence: 96%
“…a high response degree of nitrogen isotopic signatures and touristic pressure). Similar isotopic values, associated with tourism, had been detected in surface sediments of eutrophic lakes [42] and in marine macroalgae [29], [43], [44], therefore providing a proxy of the effects of tourism on water bodies. 5 CONCLUSIONS Lake Bracciano already suffers from the effect of climate change and direct water extraction and our results indicated that, during the late summer season (July and August), the nonresidents anthropic pressure on Lake Bracciano shores rapidly increased, threatening the water healthiness and ecosystem health.…”
Section: Discussionmentioning
confidence: 67%